Synthesis, Spectroscopic and In-vitro Photosensitizing Efficacy of Ketobacteriochlorins Derived from Ring-B and Ring-D Reduced Chlorins via Pinacol-Pinacolone Rearrangement - Joshi, Penny (2011)
In this report we present a regioselective oxidation of a series bacteriochlorins, which on reacting with either ferric chloride (FeCl(3)) or 2,3-dichloro-5,6-dicyanobenzoquinone (DDQ) yielded the corresponding ring-B or ring-D reduced chlorins. The effect of the number of electron withdrawing groups present at the peripheral position, with or without a fused isocyclic ring (ring-E) did not make any significant difference in regioselective oxidation of the pyrrole rings. However, depending on the nature of substituents, the intermediate bis-dihydroxy bacteriochlorins on subjecting to Pinacol-Pinacolone reaction conditions gave various ketochlorins. The introduction of the keto- group at a particular position in the molecule possibly depends on the stability of the intermediate carbocation species. The newly synthesized bacteriochlorins show strong long-wavelength absorption and produced significant in vitro (Colon26 cells) photosensitizing ability. Among the compounds tested, the bacteriochlorins containing a keto-group at position-7 of ring-B with cleaved 5-member isocyclic ring showed the best efficacy.